Transformasi Digital Sistem Rekrutmen Calon Pegawai Tenaga Kependidikan - Jesika, Jesika; Hidayati, Dian (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Starting from the difficulty of getting employees who have the right competencies in educational institutions. This research aims to determine the recruitment process digitalization for prospective employees and its challenges. The type of research chosen is qualitative research using the library research method. The results of this research are that in recruiting employees in education, the things that schools need to do are (1) look at the needs that exist in the school along with job descriptions and what skills can support the staff in completing their work; (2) the school determines where it is appropriate for job vacancies to be advertised; (3) the school selects the best qualified applicant for the vacancy; and (4) the school provides orientation or introduction to new employees so that employees can adapt quickly and the challenges faced by the school and employees in its implementation, such as (1) education staff do not receive enough attention so they are disturbed in improving their competence; (2) internal promotions prevent the school from getting more competent employees; (3) requirements such as domicile make it difficult for applicants to get jobs that match their qualifications; and (4) limited costs for start-up schools can also prevent schools from getting employees because they are not yet well known in the community.